EVALUASI SISTEM AKUNTANSI MANAJEMEN TERHADAP KELANCARAN PROSES PRODUKSI PADA PT. SEMEN BOSOWA - Edi Jusriadi; Ario Ario (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
This study aims to determine how the influence of management accounting system evaluation on the smooth process of cement production at PT. Semen Bosowa Maros. This type of research used in this research is descriptive method. Data collection techniques using observation and interviews. The results showed that PT Semen Bosowa Maros had done this well because the Management Accounting System Evaluation was carried out systematically and structured starting from the time of production planning, production process control and performance coordination. and in the annual production of PT Semen Bosowa from 2014 to 2018 decreased as an adjustment to the level of cost realization which also increased in that year.